Primary extraskeletal osteosarcoma of rectal mesentery: a rare case and literature review - Zhikui Huo; Yao Sun; Jinghui Chang; Guo-Dong Li; Jian Shi; Cheng Quan; Li-Na Zhang; Ting-Ting Yang; Feng-Jia Shang; Yong-Ping Yang (World Journal of Surgical Oncology)
Abstract Background Extraskeletal osteosarcoma (ESOS) is a rare kind of sarcoma with a low preoperative diagnosis and a poor prognosis. ESOS arising from abdominal mesentery is extremely rare. Increasing diagnostic methods and standardizing treatment protocols are crucial issues of ESOS. Case presentation We report the case of a 52-year-old female ESOS patient. She had a history of ovarian carcinoma (stage IIIC) surgery two years before, with five cycles of chemotherapy. A mass was found during postoperative examinations. A R0 surgical resection was performed. Post-operational pathological report plus intra-surgery findings supported a diagnosis of ESOS. She is still alive 10 months post-operationally, with routine blood and radiographical examinations. Conclusion Enhancing awareness of this extremely rare disease together with advancements in diagnostic methods will hopefully enable earlier recognition and initiation of treatment. Protocols for standardizing treatments require a larger multi-center collaboration and more data analysis.